THE INFLUENCE OF INTERNAL AUDITORS, INTERNAL CONTROL SYSTEM, WHISTLEBLOWING SYSTEM AND ORGANIZATIONAL COMMITMENT TO FAKE PREVENTION (FRAUD) - Hamilah, Kenny F. Sihotang (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The study aims to determine the effects of the an auditor, internal control system, whistleblowing system, and organization the commitment of deception. The independent variable in the study are internal control system, whistleblowing that a system, organizational commitment. Dependent variable is fake prevention. The purpose of this study is to examines the impact in an auditor internal fraud, fraud prevention on the internal control system (fraud prevention), also examines the impact of the fraud of system preventing the whistleblowing, commitment organization on fraud prevention. The effects of an internal auditor, internal control system, whistleblowing system, and organization commitment on fraud prevention. Population in this study all personnel work in financial accounting, auditor in company and a subsidiary of the sample PT. PERTAMINA. The sampling technique used a purposive sampling with sample of 100 respondents. The research finding is the investigation, which took place in both government and private agencies, indicates irregularities and fraud within the body or the company itself. Cheating means dishonesty and dishonesty. So it can be concluded that copy has elements of unlawful conduct, committed by people inside and outside the organization for personal or group gain, and directly or indirectly harms the other party. Auditors internal, internal control systems, and organization commitment have significantly effect on cheating prevention.